Conditions of teaching work during the Covid 19 pandemic - Edson Marcos de Anhaia; Regis Clemente da Costa (Universidade Federal do Norte do Tocantins, 2024)
The text discusses part of the results of the research "Education and Rural Schooling in the times of the Covid-19 pandemic" conducted by groups from the Rede Latino-Americana de escudos e pesquisas em Educação do Campo. Our objective is to analyze the working conditions of teachers in rural schools during the Covid-19 pandemic. We started with data resulting from interviews conducted with questionnaires and answered virtually. Out of the 645 responses we obtained, we selected 18 teachers who work in rural schools in the years 2020 and 2021. We begin the text by discussing labor and the worker, drawing on Marx, in the context of a society guided by the development model of capital. In the second part of the text, we specifically address the working conditions of teachers in rural schools during the Covid-19 pandemic; the analysis is based on the statements of the interviewees, engaging with the elements they brought forward. The precarization of work and the exhaustion of teachers during this period became evident. Finally, we present some considerations about the experiences lived by teachers during the pandemic.